Teaching literature component in English: a case study of approaches / Wan Badrolzaman Wan Muda - Wan Muda, Wan Badrolzaman (2012)
This study aimed to identify the approaches used by teachers in teaching literature component in English. It was conducted in 20 schools around Kuala Terengganu using a set of questionnaire in which total of 99 teachers responded to it. Findings show that the Information-based approach (mean = 3.91) is the most favoured by teachers in the literature classroom. This is followed by the Moral-philosophical approach (mean = 3.68) and the Paraphrastic approach (3.65). The findings draw attention to the fact that teaching approaches employed by teachers are basically teacher-centred and these findings relate well to earlier studies by Sidhu (2003) and Siti Norliana (2003). The implication is that literature teaching which aims at developing students' language and thinking skills, generating students' personal response, and creating appreciations towards literature may not be achieved if the related issues are not tackled wisely.